Formação de formadores e educação inclusiva : análise de uma experiência via internet - Dal-Forno, Josiane Pozzatti (2009)
This study aimed at analyzing both the contributions and limitations of a distance learning professional development program based on the knowledge of educators, taking inclusive education policy into account. The Program for Educating Teacher Educators was entirely developed using a distance learning mode, in a specific virtual learning environment that was designed for that purpose at the Teachers Portal of UFSCar (http://www.portaldosprofessores.ufscar.br) and was addressed to educators of teachers who work in the initial years of elementary school. The investigation was based on a constructive-collaborative model of researchintervention that stimulates collaboration among participants in a non-hierarchical relation which promotes partnership process and mutual learning. The analyzed data were produced by 16 participants during eight months of intervention. Generally they resulted from both individual and group activities performed in the virtual environment and in the respective teaching institutions. The adopted theoretical background comprises learning to teach, teacher education, teacher educators' education, inclusive education, and distance education via Internet. The results indicate that teacher educators increased their knowledge basis to work with teachers in the perspective of inclusive education. The content of such learning is related to the own acting as teacher educators in the school context, inclusive education and teacher education to encourage learning of all students. As for the specific content knowledge, the activities were related to learning how to educate and be an educator and to inclusive education, going through meanings, practices and legislation. As for the pedagogical content knowledge, it was observed that the learning occurred in different levels, evincing distinct ways of working as an educator in the perspective of inclusive education. This learning arises especially from constant support and assistance, close relation with teacher educators practice, possibilities of intervention in their contexts during this process, characteristics of employed methodology based on reflections about practice, as well as on interaction and discussion with peers. The potentialities and limitations of the implemented proposal are related to the previously mentioned factors and to obstacles in technical support. Besides that, creating space for education is one of the challenges reported by the educators because they are overburdened with administrative tasks and have difficulty performing pedagogical functions, especially supporting and assisting teachers. Considering that learning of teacher educators occurred in two different environments, school and Internet, it is essential that education proposals designed for teacher educators take into account such contexts. The complexity of current schools requires a multiplicity of formats or educational possibilities to learn and it should be considered when creating courses and formulating politics for teacher educators' education. So, it is important to consider the way teacher educators can assist teachers by identifying and eliminating barriers in students learning so that all of them learn effectively. In addition, the founded process must have a background resulting from teacher educators reflection on their practice as well as on their beliefs and concepts which, in turn, if intertwined with their knowledge, can create an inclusive school.